2020
DOI: 10.1007/s40200-020-00586-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spiritual well-being and hope, and adherence to treatment regimen in patients with diabetes

Abstract: Background Adherence to treatment regimen is one of the behaviors related to diabetes, which has predicted successful control of the disease and reduced its intensity as well as negative consequences. This study aimed to determine the relationship between spiritual well-being and hope, and adherence to treatment regimen in patients with type II diabetes referred to diabetes clinics. Methods In this descriptive-correlational study, 227 diabetic patients referred to healthcare centers and diabetes clinics affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
(58 reference statements)
3
17
1
Order By: Relevance
“…Benefiting more from economic capital is associated with meeting needs faster and increasing the chances of overcoming problems and achieving success. In another study, a direct and significant relationship was found between hope and level of income [ 32 ], which is congruent with our findings. In our study, unemployed people had hopes lower than other caregivers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Benefiting more from economic capital is associated with meeting needs faster and increasing the chances of overcoming problems and achieving success. In another study, a direct and significant relationship was found between hope and level of income [ 32 ], which is congruent with our findings. In our study, unemployed people had hopes lower than other caregivers.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the level of hope in caregivers in different groups did not differ significantly in terms of caregiver and patient gender, marital status and type of insurance. In addition, a significant association was observed between gender and marital status in dialysis patients [ 32 ]. In the Lohne study, there was no relationship between gender and hope in family caregivers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates a significant relationship between hopefulness and mental health [ 8 , 9 ]. Hope is an indicator of a person’s psychological dimensions, which relate to both mental and physical health; hope is the ability to believe in a better feeling toward the future.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence and burden of cardiovascular disease, it is important to seek solutions to help patient healing and reduce disease complications [ 3 ]. Improving quality of care and treatment through patient participation in healthcare programs can improve patients’ physical condition and, hence, reduce mortality and cost [ 4 , 5 ]. Empowering patients with cardiovascular diseases to engage in self-care could help control disease symptoms and prevent or delay disease complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%